Healthy lifestyle interventions in general practice Part 6: Lifestyle and metabolic syndrome - Martin P. Schwellnus; D.N. Patel; C.J. Nossel; M. Dreyer; S. Whitesmans; E.W. Derman (South African Family Practice)
Although there is no clarity on the precise definition of the metabolic syndrome, there is consensus that it is a cluster of inter-related risk factors (elevated blood pressure, elevated plasma glucose, atherogenic dyslipidaemia) that are due to mainly abdominal obesity and insulin resistance, and which appear to directly promote the development of atherosclerotic cardiovascular disease (ASCVD), and increase the risk for developing type 2 diabetes mellitus. The prevalence of the metabolic syndrome is increasing globally, including in the adolescent population. In developed countries the prevalence of the metabolic syndrome is about 30% of the adult population. The cornerstone of management of this syndrome is lifestyle intervention. Following a comprehensive initial assessment to risk-stratify patients, they are recommended to attend either a group-based programme (medically supervised or medically directed, depending on the severity of the disease and the presence of any co-morbidities) or a home-based intervention programme. The main elements of a lifestyle intervention programme for metabolic syndrome are nutritional intervention (mainly for weight loss and to improve the atherogenic dyslipidaemia), exercise training (minimum of 30–60 minutes at moderate intensity on most days of the week), and psychosocial interventions. Regular monitoring should be conducted and a follow-up assessment is indicated after three months to assess progress and to re-set goals. Longer-term (5–6 months) and supervised intervention programmes are associated with better long-term outcomes.